Bioleaching Process of Sewage Sludge and Anaerobically Digested Sludge via Indigenous Sulfur-Oxidizing Bacteria to Improve Dewaterability and Reduce Heavy Metal Content - Suyun Xu; Yuze Jiang; Ruixiang Zou; Xuefeng Zhu; Hongbo Liu (Fermentation)
This study investigated the role of indigenous inoculum (primarily sulfur-oxidizing Acidithiobacillus thiooxidans and other acidophilic bacteria) in heavy metal removal from sewage sludge (SS) and anaerobic digested sludge (ADS). Four treatments were evaluated: inoculum + elemental sulfur (S/ADS + E), inoculum alone (S/ADS + B), elemental sulfur alone (S/ADS + S), and a control with no additives. After 7 days of bioleaching, SS and ADS exhibited comparable heavy metal removal rates on Ni (92–98%) and Pb (88–92%), which were significantly more mobilized than Cu (30–44%) and Cr (63–73%). After bioleaching treatment, residual metals in both sludge types were predominantly sequestered in the oxidizable (F3) and residual (F4) fractions, markedly reducing their environmental mobility and pollution risk during land application. The dewaterability performance, assessed via capillary suction time (CST), reached the optimal values in S + E and ADS + E within 24–48 h, after which CST increased alongside rising extracellular polymeric substances and dissolved organic carbon. While the S/ADS + B configuration exhibited marginally reduced Cu, Ni, and Pb removal efficiencies relative to S/ADS + E, it demonstrated superior dewaterability characteristics under equivalent reaction durations. These results suggest that limiting the sulfur (S0) supply to moderate the growth and activity of autotrophic A. thiooxidans can maintain the bioleaching pH within 2.0–3.0, striking a balance between effective heavy metal removal and favorable dewatering performance.